The Processes of English Teacher Training in the Global Context (2019)
The article presents a discussion about the training process expected to be received by the future English teacher, from the perspective of the globalization, showing the demands and challenges imposed by this new condition. It shows an outline about the pedagogical implications of this event and the theoretical references that support the relationship between globalization, the characterization of this new teacher and the demands imposed by this condition, to his/her training process. The methodological process is based on the theoretical reflection of these considerations. As a result, it raises some guidelines to be taken into account in the process of training an English teacher in the global context